Pengaruh Sistem Irigasi terhadap Produksi dan Kualitas Organoleptik Tembakau - Eko Sulistyono; , Sudradjat; M. H. Bintoro; Gatot Irianto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
The objective of this research was to study the effect of irrigation system on production and organoleptic quality of tobacco. The treatments were conventional irrigation, drip irrigation with mulch and drip irrigation without mulch.  Conventional irrigation was the irrigation system that was usually applied by farmer.  Plastic pipe was used for conveying water from water resource to field, and the irrigation was given twice a week. Drip irrigation was given once in two days. Drip irrigation with mulch resulted higher sun cured leaf weight and water used efficiency than conventional irrigation, but it was not significantly different compared with drip irrigation without mulch.  Drip irrigation without mulch resulted 5.505 ton/ha of sun cured leaf and water use efficiency as much as 3.4 g of sun cured leaf/kg of water.  Organoleptic quality resulted by three irrigation systems were mild to medium, fairly smooth and low irritant.   Key words :  Drip irrigation, mulch, water use efficiency, organoleptic quality, tobacco